Diagnostic and Therapeutic Approach to HIVKaposi's Sarcoma Patients-Case Report - Charis Chari; Antonios Dalampiras; Ioanna Margianou; Katerina Zarampouka; Antonios Michalopoulos (Balkan Stomatological Society, 2019)
Background/Aim: The Acquired Immune Deficiency Syndrome (AIDS) is an immunologic entity, which is due to an RNA virus. AIDS is relatively easy transmitted and has a poor prognosis. The main mechanism of this Syndrome is characterized by the destruction and diminishing of T4 lymphocytes or helper/suppressor T-cells. Kaposi's sarcoma is a neoplasm due to human herpes HHV-8. Kaposi's sarcoma is one of the entities that determines the disease of AIDS. Kaposi's sarcoma appears as skin lesions and attacks the oral cavity and lymph nodes.